Xanthine Oxidoreductase Inhibitor Use Associated With Reduced Risk of Sarcopenia and Severe Sarcopenia in Patients Undergoing Hemodialysis - Kurajoh, Masafumi; Mori, Katsuhito; Miyabe, Mizuki; Matsufuji, Shota; Kizu, Akane; Tsujimoto, Yoshihiro; Emoto, Masanori (Frontiers in Medicine, 2022)
Background: Xanthine oxidoreductase (XOR) inhibition reduces reactive oxygen species (ROS) production and enhances adenosine triphosphate (ATP) synthesis. We investigated the protective effects of XOR inhibitor treatment on sarcopenia, frequently observed in patients undergoing hemodialysis (HD), in which increased ROS and ATP shortage are known to be involved. Methods: This retrospective cross-sectional study included 296 HD patient (203 males, 93 females). Muscle mass, physical performance, and muscle strength were assessed using dual-energy X-ray absorptiometry, five-time chair stand testing, and handgrip strength, respectively. The Asian Working Group for Sarcopenia 2019 criteria were used to define low muscle mass, low physical performance, and low muscle strength, as well as sarcopenia and severe sarcopenia. Results: Sarcopenia and severe sarcopenia prevalence rates were 42.2% and 20.9%, respectively. XOR inhibitor users (n=119) showed a significantly (p<0.05) lower prevalence of sarcopenia and severe sarcopenia, as well as reduced muscle mass, physical performance, and muscle strength than nonusers (n=177). Multivariate logistic regression analyses also revealed XOR inhibitor use to be significantly associated with low muscle mass [odds ratio (OR), 0.384; 95% confidence interval (CI), 0.183-0.806; p=0.011] and low physical performance (OR, 0.286; 95% CI, 0.142-0.578; p<0.001), while significance with low muscle strength was borderline. Furthermore, XOR inhibitor use was significantly associated with sarcopenia (OR, 0.462; 95% CI, 0.226-0.947; p=0.035) and severe sarcopenia (OR, 0.236; 95% CI, 0.091-0.614; p=0.003). Conclusions: XOR inhibitor use was significantly associated with reduced risk of sarcopenia/severe sarcopenia in HD patients, suggesting that XOR inhibitor treatment has protective effects on sarcopenia in HD patients.